The New Economic Realities and the Labor (Theoretical Concepts) - Syrova, Elka (Research Papers, 2017)
In recent years unfolds an information communication revolution, associated with significant changes in technology, software and communications, and the transition to a new type of economy, which is summarized by some authors as the "revolution of the concepts" (Р. Drucker). As a precondition and a result occur also significant changes in the place and role of humans in the production system.The goal of the current paper is to summarize the main features of the new type of economy, as in the interpretation of key concepts for it to systematize the ongoing changes in the forms of application, functions, nature and content of work.For the achievement of the basic goal and tasks of the research will be applied the traditional methods of induction and deduction, the historic and the logical approach, methods and means of the comparative analysis.The analysis leed to the conclusion that the work in the new economy differs significantly from that in the previous stages of the development of the economy. Its evolution follows the trend of more dynamic development, the use of more highly qualified staff, the increasingly widespread application of various flexible forms of employment.